A case report of primary multiple obturator nerve schwannomas. Issue 9 (September 2020) - Bai, Xuechai; Li, Yan; Li, Xiaojing; Cao, Siyu; Wang, Liang
Primary multiple obturator nerve schwannomas originate from Schwann cells and are extremely rare. Patients with schwannomas are asymptomatic and a retroperitoneal schwannoma is often misdiagnosed as an adnexal mass. In the present study, we describe a 58-year-old woman in whom a right adnexal mass accompanied by endometrial polyp was found incidentally through transvaginal ultrasound. The mass was diagnosed as multiple obturator nerve schwannomas after laparoscopy. Immunohistochemical assay confirmed the schwannomas to be positive for SOX10. To our knowledge, this is the first report to demonstrate a case of multiple schwannomas originating from the obturator nerve and treated by laparoscopic resection.